What's crucial in evaluation research: a reply to Bennett - Pawson, Ray (The British journal of criminology, 1996)
Beware researchers proclaiming an innocence in respect of methodological principles. Every nut, bolt and washer in a laboratory instrument is the carrier of epistemological assumptions. Every aspect of design, data collection and analysis in social research bears a commitment to a particular model of social explanation. This paper examines Bennett's reconstruction of his own research, detects some wishful thinking and seeks to extract from the debate further clarification on what is crucial in evaluation research